WAYS TO FURTHER IMPROVE THE ACTIVITIES OF BANKS IN THE REPUBLIC OF UZBEKISTAN - Yuldashev Farxodbek Abdumutalibovich (International Journal of Artificial Intelligence for Digital Marketing, 2024)
This article discusses the issues of further improving the activities of banks in the Republic of Uzbekistan. The banking system, as an important link in the country's economy, plays a crucial role in developing the economy through the introduction of innovative financial services, the development of digital transformation processes, and improving the quality of customer service. During the study, problems arising in banking activities were analyzed and practical recommendations were given on their solutions. In particular, important proposals were put forward on the effective use of financial resources, the introduction of modern technologies, and the improvement of the legislative framework of the banking system